MENINGKATKAN KEMAMPUAN BERBICARA MELALUI MEDIA GAMBAR BERSERI PADA ANAK USIA 4-5 TAHUN DI PAUD CAHAYA HATI KECAMATAN KAMPAR KABUPATEN KAMPAR - Ardaneti, Ardaneti; Zulkifli, Zulkifli; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in the ability to speak the children in group A through media beamed images in early childhood Cahaya Hati District Kampar regency of kampar . This study is the kind of research that use action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject use are 15 children in group A in early childhood Cahaya Hati. The research data obtained through observation and data analysis were conducted by using descriptive analysis of quantitative and qualitative. The results showed that media beamed images can improve the ability to speak in a group of children. It can be seen from the increase in the average percentage of children's speech on the first cycle of 54.05% undeveloped criteria (MB) and an increase of 38.91% in the second cycle to 75 , 08% criteria developed very well (BSB). So, media images beamed can improve speaking skills on children aged 4-5 years in early childhood Cahaya Hati District Kampar Regency of Kampar.Keywords : Speech, Media Image Serial